PERBEDAAN WAKTU KONTAK MEDIA SARING KARBON AKTIF MENGGUNAKAN GREASE TRAP TERMODIFIKASI TERHADAP KADAR MINYAK DAN LEMAK LIMBAH CAIR PENYAMAKN KULIT DI PT. GARUT MAKMUR PERKASA (Jurnal Kesehatan Siliwangi, 2021)
The liquid waste from leather tanning produced of PT. Garut Makmur Perkasa in it contains oil and fat that comes from the fleshing process. Oils and fats are classified as dangerous for aquatic life and humans if their value exceeds the quality standard. The purpose of this study was to determine the effect of variations in contact time of activated carbon media using a modified grease trap on the oil and fat content of the tannery waste water of PT. Garut Makmur Perkasa. This type of research is categorized as a field experiment with a pretest-posttest research design without control. The research population is all production waste at PT. Garut Makmur Perkasa. The sampling technique used is grab sampling or sampling at any time. The univariate analysis of this research showed that the average reduction in oil and fat content in the treatment was 1) 8,28 mg/L, 2) 15,70 mg/L and 3) 20,32 mg/L. Bivariate analysis used is one way anova test. The test results on the three variations of activated carbon contact time which were carried out 6 times showed a decrease in oil and fat content, namely at 50 minutes is 31,65%, 60 minutes is 60,70% and 70 minutes is 83,20%. The conclusion of this study is that there is an effect of differences in media contact time with oil and fat content using a modified grease trap in the liquid waste produced by PT. Garut Makmur Perkasa. Suggestions for this research are to add a grease trap and calculate the saturated mass of activated carbon.